(3fNHI GdRgQI GdKejfI aj fSH CTQGa GdeOjfIs - (3Ydj Hf GdMSf Hf TObes; (3VGef Hf TObe Hf Ydj Hf MSf Hf GdfbjH GdeOfj GdMeRj GdMSjfj, GHf TObe,J (B1088 (3g` ? s
(3ChdgG (B:s
(3HYO MeO Gddg GdhGMO GdCMO agPg fHPI GNJUQJgG ef QSGdJi RgQI Gdebhd aj fSH KGfj aQYj GdQShd s
(3BNQgG (B:s
(3hPdc GdhUd YhdJ aj HYVg Ydi NHQ TQYi hPcQJ SfOg ai GdRgQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B213s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B445 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs